Maḥmūd Muḥammad Ṭāhā dan Konsep Abrogasi dalam al-Qur’an - Iffah (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2021)
The intricacies surrounding the concept of abrogation (naskh) in the Qur’an have spurred considerable scholarly debates. Mahmūd Muḥammad Ṭāhā, an insightful contemporary thinker from Sudan, has significantly contributed to this discourse by presenting a unique perspective. Ṭāhā ‘s viewpoint posits that abrogation is not a definitive annulment of the law but rather a deferment of its application until a more opportune time. This article delves into Ṭāhā‘s novel understanding of abrogation, particularly exploring its implications concerning the implementation of Makkiyah verses and the abrogation of Madaniyah verses. It also examines Ṭāhā‘s concept as an alternative stance to the discourse of abrogation and evaluates its broader impact on Islamic law and legal methodology. Ṭāhā asserts that Makkiyah verses encapsulate the timeless and foundational message of Islam, making them pertinent for application in our pluralistic modern era. The repercussions of this theory are profound, notably influencing Islamic law, particularly in dismantling gender-based discriminatory practices like those found in inheritance laws and witness testimonies. Additionally, it challenges concepts such as dhimmī and jizyah in the context of interactions with non-Muslims. Methodologically, Ṭāhā‘s theory advocates for ijtihad across all cases, even in the presence of existing textual sources.